Theatre as a Medium to Discover a Pedagogy of Activism - Ted McCadden; Jennifer L Pemberton; Alan Chaffe (Adult Education Research Conference, 2019)
This study revisits two data sets, narratives from theatre artists exploring sexual identity and interviews with participants from queer theatre festivals, to explore experiences of activism within the participants’ reflections.
Keywords: theatre; activism; queer theory